Critical thermal limit and behavior of the Barramundi (Lates calcarifer Bloch, 1790) fingerling exposure with different temperature - Fachrurozi Amir; Firman M. Nur; Nur Fadli; Zainal Abidin Muchlisin (Depik, 2021)
Barramundi (Lates calcarifer) is one of the commercial fish in Indonesia. The phenomenon of climate change due to global warming has affected the life of aquatic biota, including fish. The objectives of the present study were to determine a critical thermal maximum (CTMax) and the behavior of Barramundi (L. calcarifer) due to the increase in water temperature. The research was conducted at the Fishing Technology Laboratory, Faculty of Marine and Fisheries, Universitas Syiah Kuala in February 2021. The experiment was conducted in 10 aquariums equipped with heaters. The initial temperature of the treatment was 28oC and increased gradually every one minute by 0.2oC. The results showed that the abnormal behavior of Barramundi fingerling was started to appear at 37oC where the fish began to swim fast, then swim sideways at 38oC-39oC, hit the container wall at 39oC-40oC, jumped and weakened then dead at 40oC and 41oC. The average critical temperature of Barramundi fingerling was recorded at a temperature of 41oC within 65 minutes. Therefore, it is concluded that the Barramundi (L. calcarifer) display an abnormal behavior above the temperature of 35oC, however, they can survive up to 42oC exposure for 70 minutes.Keywords:Critical thermal maximumTemperature riseGlobal warming